Google Wave. - McDonald, Alyssa (New Statesman, 2009)
The latest product from the developers behind Google Maps, Google Wave combines social networking, instant messaging, and emailing functionality. Google Wave allows users to leave a message for someone offline, start an online conversation, conduct an online conversation with multiple participants and more. It will also make it possible for users to share photographs, maps, weather forecasts and more, as well as enabling them to embed “robots,” or small programs similar to those available on social networking sites, into the content of the message. According to Google, the application has received a positive response from the 6,000 trial users but the real test will be on September 30, 2009, when Google will invite an additional 100,000 users to to try out Wave.